Training program on work related proper body mechanics among excellent general services employees at Pamantasan ng Lungsod ng Maynila Intramuros, Manila - Esteban, Michelle G., Lazarte, Francis C.; Ong, Joy Anthony O., Santos, Melandro R., Soriano, Raschelle S. and Wong, Rovina O. 4 0 16; 5 (2002)
u
Undergraduate (Thesis) Pamantasan ng Lungsod ng Maynila;College of Physical Therapy, Bachelor of Science in Physical Therapy
Keywords: 2 -- 0; 6; 20; 20; 2